Measurement and Correlation for Solubility of Adipic Acid in Several Solvents - 樊丽华 马沛生 相政乐 (Chinese journal of chemical engineering, 2007)
Using a laser detecting system, solubility data were measured for adipic acid dissolved in six pure solvents, namely, cyclohexanone, cyclohexanol, acetic acid, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethylsulfoxide at the temperature range from 293.15K to 353.15K. All these data were regressed by 2h, NRTL, Wilson, and the modified Wilson models. For the study of six, 2h, NRTL, and the modified Wilson models were found to provide an accurate mathematical representation of the experimental results, with overall average absolute relative deviations between measured and calculated values as 1.74%, 2.06%, and 3.06%, respectively. The results showed that the λh model is the most suitable for description of the solid-liquid equilibrium containing adipic acid.